VISITORS PERSPECTIVES TOWARDS THE CONSERVATION OF HERITAGE BUILDING: THE CASE STUDY OF GURNEY PARAGON MALL, PENANG - Abdul Latip, Normah; Md Sani@Abd Rahim, Norazmawati; Haron, Syarmila Hany; Hamzah, Rosniza; Abu Bakar, Adaweia Nuur; Umar, Mohd Umzarulazijo (PLANNING MALAYSIA, 2018)
The purpose of this paper is to acquire a better understanding of the history, background, process and impact of the restoration of St. Joseph’s Novitiate, and it integration into Gurney Paragon Mall. St. Joseph’s Novitiate has significant historical, architectural, aesthetic, archaeological, spiritual, social, political and economic value, and as such, requires continuous care and preservation. This study explores the perspectives of visitors to the shopping mall, with St. Joseph’s Novitiate having been physically integrated into the mall’s construction, and found that the conservation of heritage buildings was regarded as very important, even when a new development could easily replace the historic building. This is likely a one of a kind study because it involves a modern shopping mall attached to a UNESCO World Heritage Site building. The conservation of historical buildings carries with it a number of environmental, social and cultural impacts. Understanding these impacts is important in terms of trying to determine whether conservation efforts help to maintain the value of the heritage.